MILITARY ART OF THE ANCIENT PEOPLES OF CENTRAL ASIA - Soyibnazarov U.Sh. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article presents analytical information about the military art, weapons, and defensive structures of the ancient Central Asian peoples, including the Sakas and Massagetae , Bactrians, and Khorezmians .